2015
DOI: 10.1093/cercor/bhv234
|View full text |Cite
|
Sign up to set email alerts
|

Building by Syntax: The Neural Basis of Minimal Linguistic Structures

Abstract: Language comes in utterances in which words are bound together according to a simple rule-based syntactic computation (merge), which creates linguistic hierarchies of potentially infinite length-phrases and sentences. In the current functional magnetic resonance imaging study, we compared prepositional phrases and sentences-both involving merge-to word lists-not involving merge-to explore how this process is implemented in the brain. We found that merge activates the pars opercularis of the left inferior front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 97 publications
8
106
2
Order By: Relevance
“…This region, Brodmann area 44, has been identified as a locus of syntactic processing in numerous fMRI studies of healthy adults (Goucha & Friederici, 2015; Heim, Opitz, & Friederici, 2003; Zaccarella, Meyer, Makuuchi, & Friederici, 2015) and in studies of patients with impairments of grammatical comprehension and expression (Ash et al, 2009; Charles et al, 2014; Grossman et al, 2013; Gunawardena et al, 2010). The present study associates deficits in syntactic processing with this neuroanatomic region during active and unconstrained production of syntax.…”
Section: Discussionmentioning
confidence: 99%
“…This region, Brodmann area 44, has been identified as a locus of syntactic processing in numerous fMRI studies of healthy adults (Goucha & Friederici, 2015; Heim, Opitz, & Friederici, 2003; Zaccarella, Meyer, Makuuchi, & Friederici, 2015) and in studies of patients with impairments of grammatical comprehension and expression (Ash et al, 2009; Charles et al, 2014; Grossman et al, 2013; Gunawardena et al, 2010). The present study associates deficits in syntactic processing with this neuroanatomic region during active and unconstrained production of syntax.…”
Section: Discussionmentioning
confidence: 99%
“…This fits with the results from Schell et al (2017), who found aIFG activation for adjective-noun phrases (blue boat) versus single words (boat). Consequently, aIFG involvement might reflect increased semantic load carried by real words, which also goes beyond sentential level (Zaccarella et al, 2015), to track the amount of semantic information to be integrated.…”
Section: General Phrasal Composition Engages a Large Semantic Networkmentioning
confidence: 99%
“…This is a crucial step in the creation of the hierarchies (trees of entities) that seem necessary for the syntactic processing of language, but also for hierarchical thinking more generally (e.g., deduction, discourse, planning, story-telling, etc.). Recent fMRI experiments [40] have indicated that, indeed, the completion of phrases and sentences (the completion of auditory stimuli such as "hill top" and "ship sunk") activates parts of Broca's area -in particular, the pars opercularis BA 44 for phrases, and the pars triangularis BA 45 for sentences. In contrast, unstructured word sequences such as "hill ship" do not seem to activate Broca's area.…”
Section: Introductionmentioning
confidence: 99%